Akuntabilitas Ombudsman Republik Indonesia dalam Penyelesaian Maladministrasi Pelayanan Publik Perspektif Hukum Administrasi Negara - Citra Nasir; Andi Fatmawaty Syam (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Maladministration in public services remains a problem that has the potential to reduce the quality of governance and trigger corrupt practices. Therefore, accountable oversight is needed through the Ombudsman of the Republic of Indonesia as a public service supervisory institution. This study aims to analyze the accountability of the Ombudsman of the Republic of Indonesia in resolving public service maladministration in 2022 from the perspective of state administrative law. The study uses normative legal methods with a statutory and conceptual approach. Data were obtained through a literature review of relevant laws and regulations, legal doctrine, Ombudsman reports, and scientific literature, then analyzed descriptively and qualitatively. The results show that the Ombudsman's accountability is realized through a mechanism for receiving and examining public reports, self-initiated investigations, issuing corrective recommendations, and reporting on institutional performance. Politically, the Ombudsman has an independent position and is free from power intervention. Financially, the institution's accountability is reflected in the achievement of an Unqualified Opinion (WTP) from the Republic of Indonesia Audit Board consecutively since 2016. Legally, the Ombudsman acts as an administrative oversight instrument in preventing abuse of authority and strengthening the principles of good governance in public services.